An Experimental Examination of the Differences in Readers's Responses to Editorial versus Advertising for Travel Destinations - Holben, Sharna; De Bussy, Nigel; Dickinson, Sonia; Allert, John (Middlesex University, 2006)
The claim that editorial is superior to advertising, although commonly made by academics and practitioners alike, has received limited empirical support. The belief that editorial is more effective is strongly held, amongst others, by destination promoters, who frequently allocate considerable budgets to media 'familiarisations' in the hope of generating positive press. It was therefore decided to test claims for the promotional advantages of editorial in the context of tourism destinations. Drawing on the Elaboration Likelihood Model, attribution theories and agenda setting theory, the aim of this research was to test experimentally whether potential tourists do indeed respond more favourably to destination editorial than advertising, in relation to affective and conative impacts. A sample of 271 students was exposed to selected editorial and advertising for the destinations New Caledonia and Hong Kong, embedded in 12-page, full-colour, mock travel magazines. The study found that the editorial format was deemed to be more credible by readers than its advertising counterpart, but no direct format based differences were observed for respondents' attitudes to the brand or behavioural intentions. However, source credibility was found to be highly correlated with both brand attitude and behavioural intentions, suggesting editorial has an important indirect effect on these key dependent variables.